PERAN GURU DALAM MENINGKATKAN KEMAMPUAN BERBICARA SISWA KELAS V DI SEKOLAH DASAR - Maulana Anbiya Fajri; Hendra Budiono; Silvina Noviyanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to describe the role of teachers as facilitators, mentors, motivators and evaluators in improving the speaking skills of fifth grade elementary school students. The background of this research is based on students' low speaking skills which are characterized by a lack of courage, limited vocabulary, and difficulty in conveying ideas orally. This research uses a qualitative approach with descriptive methods. The research subjects consisted of teachers and students of class V elementary school. Data collection techniques are carried out through observation, interviews and documentation. Data analysis techniques use data reduction, data presentation, and drawing conclusions. Based on the research results, it can be concluded that the role of teachers as facilitators, mentors, motivators and evaluators plays a role and contributes significantly in improving students' speaking skills.